Development of Integrated Biology Learning Tools with Guided Inquiry Based on the Local Environmental Potential of Lake Lebo Taliwang - Ari Ashari; Fitri Rahmawati (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Contextual biology learning allows students to connect scientific concepts with real-life conditions, making the learning more meaningful and relevant to everyday life. One of the learning models that supports this is guided inquiry with the teacher acting as a facilitator. The application of guided inquiry will be more meaningful when combined with the utilization of the surrounding environment as a learning resource. This research aims to develop biology learning tools integrated with guided inquiry based on the local potential of Lake Lebo Taliwang, which meet the criteria of being valid, practical, and effective for use in biology education using the 4D development model. Data were obtained thru expert assessment stages and collected thru validation sheets. Data analysis included the analysis of expert assessment results. Based on the development results, it was found that the development of biology learning tools based on guided inquiry utilizing Lake Lebo Taliwang as a learning resource is categorized as very feasible with the following average expert assessment results: 1) average syllabus validation result of 85.9% categorized as very good; 2) average RPP validation result of 84.7% categorized as very good; and 3) average module validation result of 85.7% categorized as very good.